HUBUNGAN KECERDASAN EMOSIONAL DENGAN PARTISIPASI GURU MATEMATIKA DALAM FORUM ILMIAH*) - HERAWATY, DEWI (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2015)
The purpose of writing this article is to clarify whether there is a relationship between emotional intelligence and participation in scientific forums. This article is part of my dissertation research. The sample was 100 of 680 mathematics teachers in junior high school as a math teacher Bengkulu province. 100 teachers of mathematics as a sample selected by simple random sampling. The data was collected through a Likert scale questionnaire technique. The study was conducted by surveying methods and techniques of path analysis to test the hypothesis. The result is a high positive relationship between emotional intelligence and teacher participation in scientific forums. Keywords: Emotional Intelligence, Employee Participation *) Disajikan dalam seminar internasional di FKIP Unib 17 Januari 2015